2017
DOI: 10.1007/s11255-017-1763-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of immune factor between patients with chronic prostatitis/chronic pelvic pain syndrome and the healthy volunteers

Abstract: Differential levels of IgG and CD8 between CPPS patients and healthy volunteers suggest a contributing role of immune mechanisms to the development of CP/CPPS; and IgG may play an important role in inflammatory CPPS. Clinical Study registration number ACTRN12613000792729.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Therefore, bacterial infection plays an important role in the initiation, neurologic and organ-specific manifestations CP/CPPS due to the reactions of cell immunity, activation of mast cells and peripheral neurons. 19,20 Our study showed that the prevalence of the UPOINT infection clinical phenotype was no more than 14% of cases after conducting multimodal UPOINT-guided therapy and was mainly related to the presence of resistant strains of microorganisms. The UPOINT infection domain before treatment was observed in 95% and 40% cases for the I and II groups, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, bacterial infection plays an important role in the initiation, neurologic and organ-specific manifestations CP/CPPS due to the reactions of cell immunity, activation of mast cells and peripheral neurons. 19,20 Our study showed that the prevalence of the UPOINT infection clinical phenotype was no more than 14% of cases after conducting multimodal UPOINT-guided therapy and was mainly related to the presence of resistant strains of microorganisms. The UPOINT infection domain before treatment was observed in 95% and 40% cases for the I and II groups, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Our team previously investigated expressions of immune markers closely associated with autoimmunity including IgA, IgM, IgG, CD4 + and CD8 + in both CP/CPPS patients and healthy volunteers (41). We found that the CP/CPPS patients had lower serum CD8 + and higher serum IgG levels than healthy volunteers.…”
Section: Discussionmentioning
confidence: 84%
“…Immune disorders and autoimmunity activation have been hypothesized to contribute to the development of CP/CPPS. 18 The estab- in patients with rheumatoid arthritis, 31,32 Crohn's disease, 33,34 psoriasis 35,36 and atopic dermatitis, 37,38 whereas it is down- when we performed the flow cytometry, we used the PMA to stimulate the T cells that could result in the endocytosis of CD4, causing potential bias. This kind of bias could be removed when the two groups used the same wayy.…”
Section: Discussionmentioning
confidence: 99%